IN THE CONTEXT OF GLOBALIZATION, THE EMERGENCE OF INTERNATIONAL SETTLEMENTS AND THEIR FORMS, AS WELL AS CURRENCY RISK - Tokhtayeva Umida Shamsiddin kizi (Web of Journals Publishing, 2024)
The article presents an analysis of various methods of classification of payment system risk management tools. The study also extensively covered how payment systems implement risk management methods in our country and abroad. The main purpose of conducting this research is to correctly assess and manage the risks in today's developing market of payment systems. Also, in this article, ways to improve risk management in payment systems are systematically analyzed and the necessary recommendations and conclusions are drawn up.
Keywords: Payment system, risk management, classification, systematization method, foreign experience, local systems.